2014
DOI: 10.1002/tox.21987
|View full text |Cite
|
Sign up to set email alerts
|

Nonylphenol regulates cyclooxygenase-2 expression via Ros-activated NF-κB pathway in sertoli TM4 cells

Abstract: The aim of this study was to investigate the signaling pathways involved in the cyclooxygenase (COX)-2 regulation induced by nonylphenol (NP) in mouse testis Sertoli TM4 cells. Our results showed that treatment of TM4 cells with NP increased COX-2 protein expression and interleukin-6 (IL)-6 and prostaglandin E2 (PGE2) secretion in a dose-dependent manner. Pretreatment with reactive oxygen species (ROS) scavenger, N-acetylcysteine (NAC), attenuated NP-induced ROS production, COX-2 expression, and IL-6 and PGE2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Indeed, in this case, NAC can mitigate azole-induced inflammatory effects. These results are in line with Liu and colleagues [ 77 ], who reported the ability of nonylphenol (NP) to increase COX-2 expression via ROS-dependent pathways in TM4 SCs.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, in this case, NAC can mitigate azole-induced inflammatory effects. These results are in line with Liu and colleagues [ 77 ], who reported the ability of nonylphenol (NP) to increase COX-2 expression via ROS-dependent pathways in TM4 SCs.…”
Section: Discussionsupporting
confidence: 92%
“…When this balance is perturbed, it causes oxidative damage 46 . Studies have shown that a variety of herbicides can increase the level of ROS, decrease the activity of SOD and GSH‐Px, and increase the content of MDA in TM4 cells 47–49 . Our results showed that the level of ROS in TM4 cells increased after exposure to 2,4‐D in a dose‐dependent manner.…”
Section: Discussionmentioning
confidence: 50%
“…46 Studies have shown that a variety of herbicides can increase the level of ROS, decrease the activity of SOD and GSH-Px, and increase the content of MDA in TM4 cells. [47][48][49] Our results showed that the level of ROS in TM4 cells increased after exposure to 2,4-D in a dose-dependent manner. At the same time, the activities of SOD and GSH-Px in TM4 cells decreased and the content of MDA increased in all exposed groups.…”
Section: Discussionmentioning
confidence: 51%
“…A widely used antioxidant, NAC, directly stimulates cellular GSH synthesis and curtails ROS production [59]. Accordingly, NAC mitigates impairment in the nonylphenol-exposed mouse Sertoli cell line (TM4) by reducing ROS production [60]. This study utilized optimal NAC treatment concentrations and durations based on established literature [30,[61][62][63].…”
Section: Discussionmentioning
confidence: 99%